La' Villagers' Rice Restaurant / Nor Aziah Md Desa ... [et al.] - Md Desa, Nor Aziah; Abdul Rahman, Noor Azlin; Abdullah, Siti Norazwani; Mohamad Sirat, Nur Irinah; Muhammad, Siti Nor Shakirah (2002)
La' Villagers' Rice Restaurant is a business that provides a food and service. This business is very potential to be form because it is only restaurant that provide Malay food that base on rice generally in Georgetown. We also provide service to take away the food from our restaurant in fulfil needs of our customers. This business formed as a partnership. There are five important persons in the born of La' Villagers' Rice Restaurant, who are being as business backgrounds of our business. Our General Manager is Nor Aziah bt Md Desa, Administration Executive is Noor Azlin bt Abdul Rahman, Marketing Executive is Siti Norazwani bt Abdullah, Operational Executive is Nur Irinah bt Mohamad Sirat, and last but not least, Siti Nor Shakirah bt Muhamad as the Financial Executive. Our total contribution on capital is RM 107205. It present that our General Manager contribute RM 25729.20 (24%) and all other partners will contribute RM 20368.95 (19%) each. All the partners have very good qualification and have experience in working fields. Moreover, we have our own staffs that are very attitude in playing their roles. The cooperation between partners and staff will gain the effective and efficiency of our restaurant. Our business allocated at No. G 05 & 06, Prangin Mall, 10000 Jalan Ria, Penang. We decided to choose this location the location is very strategic. There are many facilities that can fulfil the needs from our customers. It has basic facilities such as shops, bus station, parking lot, and police station. Others facilities are offices such as Municipal Council of Penang Island and the nearby shopping complex such as KOMTAR.